Illocutionary Acts in Online Airline Advertising Slogans - Isnain Arrosid; Aris Munandar (Lexicon, 2018)
This research attempts to examine the illocutionary acts used in airline slogans taken from online airlines advertisements and investigate the most dominant illocutionary acts used in the slogans. The data were collected from online advertisements from November 2015 until January 2016. The results of the research show that four types of illocutionary acts are used in the slogans: directives, expressives, commissives and assertives with three patterns of illocutionary acts: Assertives entailing expressives, commissives entailing expressives and directives entailing expressives. Based on the findings, the most dominant type of illocutionary acts used was assertives with 40 occurrences (70%). Claiming is an assertive illocutionary act that was used most frequently in the slogans. This is in line with the main aim of advertising, i.e., persuading people. No declarative illocutionary act was found in the slogans since it is hard to fill the mode of achievement of a declarative in online advertising which changes the hearer’s status.